FGFR2 Promotes Gastric Cancer Progression by Inhibiting the Expression of Thrombospondin4 via PI3K-Akt-Mtor Pathway - Tingting Huang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Fibroblast growth factor receptor 2 (FGFR2) has attracted considerable interest as a therapeutic target in gastric cancer (GC). There is growing evidence to suggest that the bioavailability of the potent pro-tumor function of FGFR2 is associated with thrombospondins (TSPs). As a follow-on from our previous study, here we evaluated the potential clinical significance and mechanism of the relationship between FGFR2 and TSP4 in GC. Methods: Expression levels of FGFR2 and TSP4 were detected by immunohistochemistry in GC tissue microarray slides. SGC7901 and MKN28 cell lines were used to confirm the relationship between FGFR2 and TSP4. In vitro cell viability, colony formation, and invasion and migration assays were performed to evaluate the effect of FGFR2-TSP4 axis on tumor cell activities. The mechanism of TSP4 regulated by FGFG2 was explored via small molecular inhibitors in vitro and a xenograft model. Results: FGFR2 was shown to be markedly overexpressed in GC tissues and was correlated with a high risk of lymph node metastasis, late clinical stage, and poor prognosis. Low TSP4 expression was associated with shorter overall survival (OS) and advanced stage in GC patients. Interestingly, correlation analysis indicated that FGFR2 was negatively associated with TSP4. Indeed, in vitro and in vivo experiments suggested FGFR2 activation could downregulate TSP4 expression, which played an important role in the proliferation, invasion and migration of GC cells. We also found involvement of the PI3K-AKT-mTOR pathway in the FGFR2-TSP4 axis. Conclusion: The FGFR2 signal promotes human GC progression through the downregulation of TSP4 via PI3K-AKT-mTOR pathway. Our findings provide a foundation for further investigating promising therapeutic strategies for GC overexpressing FGFR2.